2021
DOI: 10.1590/0034-7167-2020-0524
|View full text |Cite
|
Sign up to set email alerts
|

Health care network (dis)articulation in late and moderate prematurity

Abstract: Objective: to analyze the Health Care Network (dis)articulation of late and moderate premature infants in the first year of life. Method: a qualitative study with semi-structured interview, which addressed the care network constitution in a municipality in southern Brazil. Fifteen mothers of infants participated. Thematic content analysis and flowchart were used to describe networks and services. Results: first contact in Primary Health Care is a decisive factor for the recognition and articulation of neonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
5
0
3
Order By: Relevance
“…Na presente pesquisa, uma das mães relata dificuldade de comunicação com os profissionais da unidade neonatal, nesse âmbito a fala deu ênfase ao profissional médico. Contudo, investigação desenvolvida na região sul do Brasil evidenciou que este profissional é fonte de confiança para famílias de RNPT no atendimento após a alta 19 . A comunicação profissional está dentre as diferentes estratégias que facilitam o processo de alta da UTIN, bem como a inclusão e envolvimento dos pais nos cuidados da criança, de maneira que as necessidades de ambos sejam atendidas 20 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Na presente pesquisa, uma das mães relata dificuldade de comunicação com os profissionais da unidade neonatal, nesse âmbito a fala deu ênfase ao profissional médico. Contudo, investigação desenvolvida na região sul do Brasil evidenciou que este profissional é fonte de confiança para famílias de RNPT no atendimento após a alta 19 . A comunicação profissional está dentre as diferentes estratégias que facilitam o processo de alta da UTIN, bem como a inclusão e envolvimento dos pais nos cuidados da criança, de maneira que as necessidades de ambos sejam atendidas 20 .…”
Section: Discussionunclassified
“…Achado semelhante foi evidenciado em outra pesquisa realizada com mães cuidadoras de prétermos extremos em Minas Gerais, cujas participantes enfrentaram dificuldades de acesso a serviços de saúde especializados, recorrendo ao uso de serviços de saúde privados para suprir as fragilidades do atendimento 3 . As famílias participantes neste estudo realizaram também acompanhamento no ambulatório de neonatologia do hospital universitário, local que já foi considerado referência para familiares de pré-termos em situações de afecções agudas e crônicas, e que possui o profissional médico, relatado em outra investigação como único profissional de confiança da família em algumas situações 19 . A certeza da presença do médico, nem sempre encontrado na APS, evoca a ideia de que a família tem sua rede articulada maior participação nos serviços da atenção secundária e terciária, em detrimento de maior e possível participação da primária.…”
Section: /15unclassified
See 1 more Smart Citation
“…In the present research, one of the mothers reports difficulty in communicating with the professionals of the neonatal unit, in this context, the speech gave emphasis to the medical professional. However, research carried out in the southern region of Brazil showed that this professional is a source of confidence for families of PTNBs in post-discharge care 19 . Professional communication is among the different strategies that facilitate the discharge process from the NICU, as well as the inclusion and involvement of parents in the care of the child, so that the needs of both are met 20 .…”
Section: Discussionmentioning
confidence: 99%
“…A similar finding was evidenced in another study carried out with mothers who were extreme preterm caregivers in Minas Gerais, whose participants faced difficulties in accessing specialized health services, resorting to the use of private health services to make up for the weaknesses in care 3 . The families participating in this study also underwent follow-up at the neonatology outpatient clinic of the university hospital, a place that has already been considered a reference for family members of preterm infants in situations of acute and chronic conditions, and is where the medical professional, reported in another investigation as the only professional family trust in some situations 19 . The certainty of the physician's presence, not always found in PHC, evokes the idea that the family´s network is connected with greater participation in secondary and tertiary care services, to the detriment of greater and possible participation of the primary.…”
Section: /15mentioning
confidence: 99%